Passive Sliding Mode Controlled UPFC and its Treatment Strategy of Unbalanced Grid Conditions - Chen, Yang; Wang, Han; Zhu, Miao; Liu, Ming; Ma, Jianjun; Cai, Xu (Frontiers in Energy Research, 2021)
Modular multilevel converter based unified power flow controller (MMC-UPFC) can provide flexible power regulation and plays an important role in the smart grid and future distribution networks. PI controller is widely adopted in the Unified power flow controller (UPFC) control. However, it is often difficult to figure out a pair of stable control parameters with good dynamic performance. A passive sliding mode control strategy of MMC-UPFC is proposed in this paper to achieve the advantages of both the passive controller and sliding mode controller. The proposed passive sliding mode control strategy has a fast response speed and is not sensitive to system parameter variation. Since unbalance grid voltage conditions are common in the modern distribution networks, an unbalanced grid treatment strategy is also presented with the series side of MMC-UPFC. Negative sequence components of the grid voltages are detected by the cross-decoupling method with second order generalized integrator and then compensated by the series side of MMC-UPFC. The series side converter controls the power flow and treats unbalanced grid conditions simultaneously. The efficiency of the general device is increased thus. A 27-level MMC-UPFC simulation system is built based on the Shanghai UPFC Project and validate the proposed approach.